2010
DOI: 10.1007/s00464-010-1229-1
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted gastrojejunal anastomosis does not improve the results of the laparoscopic Roux-en-Y gastric bypass

Abstract: Background Traditional laparoscopic surgery presents some difficulties for morbidly obese patients due to limited motion of instruments related to a thick abdominal wall, intraabdominal fat, and a large hepatic left lobe, with consequent loss of dexterity and greater musculoskeletal discomfort. Robotic technique could potentially overcome these limitations. This study aimed to evaluate robot-assisted laparoscopic Roux-en-Y gastric bypass in morbidly obese patients and to compare the results of robotic assistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 43 publications
3
53
0
Order By: Relevance
“…Recent studies have demonstrated that the robotic approach does not provide an advantage over laparoscopy [10][11][12][13]. Even 20 of the initial robot-assisted gastrectomies had results similar to those for experienced laparoscopically assisted gastrectomies in one report [14].…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have demonstrated that the robotic approach does not provide an advantage over laparoscopy [10][11][12][13]. Even 20 of the initial robot-assisted gastrectomies had results similar to those for experienced laparoscopically assisted gastrectomies in one report [14].…”
Section: Discussionmentioning
confidence: 98%
“…A single randomized trial exists showing equivalent outcomes [57]. Other large trials include case control studies with up to 400 patients per group or case series (one including over 1000 robotic RYGB) [58][59][60][61][62][63][64][65][66][67][68][69]: These studies all confirm non-inferiority of the robotic approach, and most demonstrate some benefit when compared with laparoscopy in reduction in gastrojejunal (GJ) leak rates, reduced strictures rates, or reduced length of stay. Data also consistently show longer operative times in the robotic groups.…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…The study by Scozzari et al [1] tried to assess the value of the robotic procedure by comparing a cohort of 110 consecutive robotassisted gastric bypasses with 423 consecutive laparoscopic RYGBPs performed at two different centers over a period of 3 years. They concluded that even though robot assistance achieves the same short-term outcomes with respect to weight loss, postoperative morbidity and length of hospital stay, the robotic approach is diminished by longer operative time and higher hospital costs.…”
mentioning
confidence: 99%
“…We read with interest the article by Scozzari et al [1], which reports the results of a retrospective comparison between laparoscopic and robot-assisted gastric bypass. During the last 5 years the increased interest in robotic surgery did not spare the field of bariatric surgery, and several comparative studies between laparoscopic and robotic or robot-assisted Roux en-Y gastric bypass (RYGBP) have been carried out, searching for potential improvements in the outcomes of standard laparoscopic RYGBP [2][3][4][5][6].…”
mentioning
confidence: 99%